2020
DOI: 10.1212/nxg.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk scores of several subtypes of epilepsies in a founder population

Abstract: ObjectivePolygenic risk scores (PRSs) are used to quantify the cumulative effects of a number of genetic variants, which may individually have a very small effect on susceptibility to a disease; we used PRSs to better understand the genetic contribution to common epilepsy and its subtypes.MethodsWe first replicated previous single associations using 373 unrelated patients. We then calculated PRSs in the same French Canadian patients with epilepsy divided into 7 epilepsy subtypes and population-based controls. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
4
16
0
Order By: Relevance
“…The total community sample comprises the 80 community controls, 125 community cases, and 69 individuals with suspected histories of mood or psychotic disorders. One UKB control and one community case have high FROH; these individuals also have the highest diagonal values of the GRM, consistent with a higher coefficient of relationship between parents single multigenerational pedigree from Spain (Collins et al, 2013), and possibly for the high rates of epilepsies reported in the French Canadian community (Moreau et al, 2020). Here, a polygenic founder effect can be considered, while recognizing the participants were ascertained based on having a mood disorder diagnosis or being a relative of a community member with a mood disorder.…”
Section: Discussionsupporting
confidence: 54%
“…The total community sample comprises the 80 community controls, 125 community cases, and 69 individuals with suspected histories of mood or psychotic disorders. One UKB control and one community case have high FROH; these individuals also have the highest diagonal values of the GRM, consistent with a higher coefficient of relationship between parents single multigenerational pedigree from Spain (Collins et al, 2013), and possibly for the high rates of epilepsies reported in the French Canadian community (Moreau et al, 2020). Here, a polygenic founder effect can be considered, while recognizing the participants were ascertained based on having a mood disorder diagnosis or being a relative of a community member with a mood disorder.…”
Section: Discussionsupporting
confidence: 54%
“…The results could imply that drug response is a far more complex trait with multiple influencing parameters beyond genomic factors alone. While PRS for epilepsy is a reliable predictor for the risk of epilepsy and epilepsy sub-phenotypes itself ( Leu et al, 2019 ; Moreau et al, 2020 ), this approach was not beneficial to predict drug response within this study's limitations.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies support the contributions of common variants to the predisposition to generalized epilepsies with different weights from different variants based on the epilepsy subtypes. 7,8 In addition, there is some evidence that the same set of common variants can affect the clinical presentation of monogenic and non‐monogenic neurodevelopmental disorders. 9 Thus, we cannot exclude the possibility of the polygenic risk contribution to the intrafamilial variability.…”
Section: Discussionmentioning
confidence: 99%